Determining the Effect of Psychological Resilience on Death, the Fear of Death, and Death Acceptance in Nursing Students in Turkey - Durmus Iskender, Mahinur; Ulaş Karaahmetoğlu, Gülşen (SAGE Publications, 2024)
This study will investigate the effects of psychological resilience on death, fear of death and acceptance of death in nursing students. This study was descriptive and cross-sectional. The sample of the study consisted of 270 students who voluntarily participated. The data were collected using a descriptive characteristics questionnaire, the resilience scale for adults (RSA) and the multidimensional orientation to death and dying inventory MODDI-F. A positive and significant correlation was found between the Acceptance Subscale, RSA and MODDI-F subscale scores. Nursing students’ attitudes towards death and dying are affected by their psychological resilience. Psychological resilience should be increased because nursing students are candida for future caregivers. For this reason, within the scope of the findings of the study, it is recommended that during the theoretical and practical nursing education process, students should be reinforced by conducting studies on the dying patient through educational teaching methods such as role play and case presentations. In addition, ıt is thought that an interview or focus group on nursing students’ psychological resilience and attitudes towards death can provide a more comprehensive source of information on the subject.
Keywords: 3. Good health